The Concept of Tauhid and Adab in the Malay World: A Review of the Epistemology of Islamic Educational Philosophy - Rini Nopita; Haris Riadi; Azizah Azizah; Sulastri Sulastri (LPPM Institut Pendidikan Nusantara Global, 2026)
Islamic education has two main pillars, namely monotheism and adab, which are the foundation in shaping individual character and knowledge. Tawhid instills awareness of the oneness of Allah as the main basis for pursuing knowledge, while adab is a moral guideline that ensures that knowledge is practiced responsibly and ethically. In the tradition of Islamic education in the Malay world, the integration between tauhid and adab has been inherited by scholars who emphasize the importance of a balance between knowledge, faith, and morals. However, in the era of globalization, this concept faces great challenges due to the secularization of education and rapid technological development. Therefore, it is necessary to revitalize Islamic education based on monotheism and adab through strengthening the curriculum, innovating learning methods, and increasing awareness of the importance of Islamic values in the world of education. Thus, Islamic education can continue to contribute to producing a generation that has intellectual intelligence as well as high moral and spiritual integrity.